An overview of the guideline from the British Society of Echocardiography 2020: what’s new? - T.M. Babkina; G.S. Smyrnova; O.V. Polishchuk; L.Yu. Hladka (Medičnì Perspektivi)
Quantitative assessment of cavities and heart function is the most common task of echocardiography (EchoCG). It is difficult to overestimate the importance of standardizing EchoCG measurements, because their results influence clinical decisions. In January 2015, the American Society of Echocardiography and the European Association of Cardiovascular Imaging, published an update Recommendations for Cardiac Chamber Quantification by Echocardiography in Adults. Since then, the results of new research using obtained prospective data, on the basis of which in February 2020 the British Society of Echocardiography (BSE) released a new guide. The authors of the recommendations set the goal of creating a simple, practical reference document and guide for everyday use that encourage the holistic interpretation of measurements (no single number should define normality or pathology). Based on these data, we considered the rational component of the updated recommendations, focused on important conceptual changes in the assessment of heart structure and function, provided new terminology for left ventricular function and left atrial size, and a new approach in assessing aortic root, right heart and left atrium. The BSE recommends obtain left ventricular dimensions from the parasternal long-axis window preferentially using 2D imaging. Aortic dimensions should be obtained using the “inner-edge to inner-edge” technique in end-diastole. The BSE suggests that for those Echocg labs that currently use the “leading-edge to leading-edge” technique, it is reasonable to continue doing so for continuity and consistency.